2017
DOI: 10.3233/jnd-160198
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of Prevalence Studies of Sporadic Inclusion Body Myositis

Abstract: There was high variability in reported sIBM prevalence estimates and the quality of the studies conducted. Existing evidence suggests an increase of prevalence estimates over time, which may be explained by growing disease awareness, improvements in diagnostic criteria and study methodologies. Further high quality studies are needed to understand if prevalence varies across geographies or ethnicities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 23 publications
2
42
0
Order By: Relevance
“…[1][2][3] Results from a systematic review and meta-analysis in people of all age categories showed that the pooled metaprevalence of IBM was 24•8 per million (95% confidence interval [CI], 20•0-29•6), when limited to the highest quality prevalence papers (data from nine articles). 4 IBM affects men more often than women (ratio: 2:1 to 3:1). 5 The progression of leg weakness leads to frequent falls 6 and results in the loss of ambulation, leading to the use of assistive devices for mobility and eventual wheelchair dependence.…”
Section: Introduction (3598 Words; Limit 4500)mentioning
confidence: 99%
“…[1][2][3] Results from a systematic review and meta-analysis in people of all age categories showed that the pooled metaprevalence of IBM was 24•8 per million (95% confidence interval [CI], 20•0-29•6), when limited to the highest quality prevalence papers (data from nine articles). 4 IBM affects men more often than women (ratio: 2:1 to 3:1). 5 The progression of leg weakness leads to frequent falls 6 and results in the loss of ambulation, leading to the use of assistive devices for mobility and eventual wheelchair dependence.…”
Section: Introduction (3598 Words; Limit 4500)mentioning
confidence: 99%
“…The prevalence of sIBM is thought to range from 4.9 to 33 per million and up to 51.3 per million in those above the age of 50 (1). However, in the absence of a reliable diagnostic biomarker, the prevalence is suspected to be underestimated due to diagnostic challenges in differentiating sIBM from other IIMs (3). Previous reports have suggested diagnostic criteria for sIBM, although the highest diagnostic sensitivity and specificity requires a combination of clinical, electrodiagnostic and pathological assessment (1, 2).…”
Section: Introductionmentioning
confidence: 99%
“…The Methodological Evaluation of Observational Research (MORE) checklist [21] was used to verify methodological quality and risk of bias. This checklist was designed for quality and bias assessment in incidence or prevalence studies of chronic diseases, and was previously used in several systematic reviews [22][23][24][25][26][27][28]. Two authors (M.C.B., H.F.L.)…”
Section: Data Extractionmentioning
confidence: 99%